5x-2x+x=9+3x+10

Simple and best practice solution for 5x-2x+x=9+3x+10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-2x+x=9+3x+10 equation:


Simplifying
5x + -2x + x = 9 + 3x + 10

Combine like terms: 5x + -2x = 3x
3x + x = 9 + 3x + 10

Combine like terms: 3x + x = 4x
4x = 9 + 3x + 10

Reorder the terms:
4x = 9 + 10 + 3x

Combine like terms: 9 + 10 = 19
4x = 19 + 3x

Solving
4x = 19 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
4x + -3x = 19 + 3x + -3x

Combine like terms: 4x + -3x = 1x
1x = 19 + 3x + -3x

Combine like terms: 3x + -3x = 0
1x = 19 + 0
1x = 19

Divide each side by '1'.
x = 19

Simplifying
x = 19

See similar equations:

| 9(8+8g)= | | 20-2(1/2) | | 3(9x+2)+8-16x= | | .5x+.1x=8 | | 6/12÷6/6 | | 5a^2-4ab+16b=0 | | 2.3=43.7 | | 4(6-2y)=64 | | 5a^2-4ab-16b=0 | | -6=x/9-7 | | 5/4x=9/4 | | 30+(4x+20)+(x+5)=180 | | 7(-9t+-9)+t= | | 3x-6-4x+9= | | 2+6n=18 | | 6n-12=96 | | 34c-13=55 | | 34c-13=15 | | 9tanx+2=7 | | W=3a-5n | | (2x-8)(x)=330 | | 20/(4-(10)) | | -22+2x=-8 | | 6r+29=83 | | 3x-6y=-3(30) | | C=F-32/1.8 | | Y=in(x+3) | | 8(4x+5y)=(5y*8)+4 | | 6+2x=5+7x | | 8h+7=127 | | 128=8y+2(x) | | 8+x+5=8+x+5 |

Equations solver categories